Crucial Breakthrough of Functional Persistent Luminescence Materials for Biomedical and Information Technological Applications - Tan, Huaxin; Wang, Taoyu; Shao, Yaru; Yu, Cuiyun; Hu, Lidan (Frontiers in Chemistry, 2019)
Persistent luminescence is a phenomenon in which luminescence is maintained for minutes to hours without an excitation source. Owing to their unique optical properties, various kinds of persistent luminescence materials (PLMs) have been developed and widely employed in numerous areas, such as bioimaging, phototherapy, data-storage, and security technologies. Due to the complete separation of two processes¬, —excitation and emission—, minimal tissue absorption and negligible autofluorescence can be obtained during biomedical fluorescence imaging using PLMs. Rechargeable PLMs with super long afterglow life provide novel approaches for long-term phototherapy. Moreover, owing to the exclusion of external excitation and the optical rechargeable features, multicolor PLMs, which have higher decoding signal-to-noise ratios and high storage capability, exhibited an enormous application potential in information technology. Therefore, PLMs have significantly promoted the application of optics in the fields of multimodal bioimaging, theranostics and information technology. In this review, we focus on the recently developed PLMs, including inorganic, organic and inorganic-organic hybrid PLMs to demonstrate their superior applications potential in biomedicine and information technology.